Analiza dokumentów strategicznych Unii Europejskiej: Human Security jako paradygmat unijnej polityki przeciwdziałania terroryzmowi - Tereszkiewicz, Filip (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
This paper analyses European Union strategic documents for evidence that EU counterterrorism policy is founded on the Human Security HS approach. It concentrates on three main strategic documents: the EU Counter-Terrorism Strategy 2005, the European Agenda on Security 2015, and the EU Global Strategy 2016 which define the EU’s current approach to terrorism. Three determinants are established to research whether counterterrorism policy is founded on the HS paradigm: a people-centred approach, the presence of a wide range of threats, and a strong presence of non-state actors. The analysis shows that counterterrorism policy is constructed on the HS paradigm, however with strong and influential leverage from member states. This paradigm was chosen by EU institutions because it guarantees a strong position of EU agencies in contrast to the traditional member state-centred approach to security. It helps also to show that EU security policy makes citizens a priority, which could increase legitimacy of the EU in the eyes of its people.
Keywords: polityka bezpieczeństwa UE; terroryzm; bezpieczeństwo ludzkie